2020
DOI: 10.46497/archrheumatol.2020.7416
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Serum Angiogenic Factor Levels and Disease Activity in Rheumatoid Arthritis

Abstract: Objectives: This study aims to evaluate the relationship between serum angiogenic factor levels and disease activity in patients with rheumatoid arthritis (RA) using both clinical and dynamic wrist magnetic resonance imaging (MRI) data. Patients and methods: Simultaneous serum angiogenesis markers [vascular endothelial growth factor (VEGF), angiopoietin-1 (ANG1), ANG2, and tyrosine-protein kinase receptor for angiopoietin (Tie-2)] were studied in 40 patients with RA (13 males, 27 females; mean age 51.1±10.8 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…These data suggest that VEGF may be one more serological inflammatory marker of autoimmune arthritis activity, and may possibly play a role in the differential diagnosis of early UA. Similar to our results, other studies confirmed no significant association between VEGF levels and DAS 28, HAQ, and VAS, the duration of morning stiffness, or the number of tender joints [83,84]. In this study, we demonstrated that patients who had a higher number of swollen joints (both 66 SJC and 28 SJC) and higher scores of synovitis and PD seen on US had statistically higher VEGF levels.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These data suggest that VEGF may be one more serological inflammatory marker of autoimmune arthritis activity, and may possibly play a role in the differential diagnosis of early UA. Similar to our results, other studies confirmed no significant association between VEGF levels and DAS 28, HAQ, and VAS, the duration of morning stiffness, or the number of tender joints [83,84]. In this study, we demonstrated that patients who had a higher number of swollen joints (both 66 SJC and 28 SJC) and higher scores of synovitis and PD seen on US had statistically higher VEGF levels.…”
Section: Discussionsupporting
confidence: 91%
“…A tendency was seen in that anti-CCP positive patients had higher VEGF values compared with negative, but they were not significant. Some authors confirmed a significant correlation between anti-CCP and VEGF [83,84], but there are also studies that detected no significant difference between VEGF levels and anti-CCP-positive and anti-CCP-negative RA patients [84]. These data suggest that VEGF may be one more serological inflammatory marker of autoimmune arthritis activity, and may possibly play a role in the differential diagnosis of early UA.…”
Section: Discussionmentioning
confidence: 88%
“…Moreover, the VEGF family has also been linked to inflammation, even in healthy individuals [54] . However, another recent publication did not find any significant correlation between VEGF and disease activity, leading to uncertain conclusions [55] . Nevertheless, our group of patients underwent extensive treatment at the time of inclusion, which may have influenced our results.…”
Section: Discussionmentioning
confidence: 96%